On “Multitude” and the Urban Question: Reading in Times of Pandemics - Abidin Kusno (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2023)
“Multitude” is a term popularized by Antonio Negri and Michael Hardt to conceptualize the labor condition and its political possibilities in the post-Fordist regime of capital accumulation. This paper seeks to explore such a concept in the context of an Indonesian city. It argues that the Indonesian multitude is formed through the worldwide division of labor, which involves the urban majorities whose work cut across formal and informal sectors. It teases out the absence of the “urban question” in the Indonesian city as a context for understanding the challenges faced by the Indonesian multitude. The paper (in light of post-pandemic) calls for the role of the state to serve as a medium for achieving societal goals and a guarantor of public access to Universal Basic Assets covering education, health, housing, technology, and information.